Urinary iodine level and its determinants in pregnant women of Shanghai, China. Issue 9 (8th April 2015) - Wei, Zhenzhen; Wang, Weiye; Zhang, Jun; Zhang, Xiaohua; Jin, Longmei; Yu, Xiaodan
Abstract : It is known that iodine deficiency during pregnancy can interfere with normal fetal growth and development. However, iodine levels of pregnant women in Shanghai, China, and factors that could influence its levels remain unclear. A total of 916 pregnant women were selected from the Maternal and Child Care Service Centre of Minhang District in Shanghai. Morning urinary iodine (UI) and iodine content of salt from the participants' home were measured, and UI concentration was adjusted by creatinine concentrations. Serum tri-iodothyronine, thyroxin, free tri-iodothyronine, free thyroxine and thyroid-stimulating hormone were tested in the second trimester of pregnancy by time-resolved fluoroimmunoassay. The median levels of UI in pregnant women were 156·3, 176·9 and 175·1 μg/g creatinine in the first, second and third trimesters of pregnancy, respectively. The prevalence of UI deficiency (UI < 150 μg/g creatinine) was 48·3, 34·2 and 36·2 % in the three trimesters of pregnancy, respectively. Factors that significantly influenced the UI levels include the following: iodine content of household salt; age; occupation; multivitamin supplement with iodine; seaweed intakes. Furthermore, UI and iodine content of salt were moderately correlated ( r 0·406, P < 0·001). In addition, there was no significant association between UI and thyroid hormone levels. The present study showed a high prevalence of UI deficiency in pregnant women in Shanghai, especially during the first trimester of pregnancy. Both iodine content of household salt and multivitamin supplement with iodine are the main determinants of UI levels in Shanghai.